(untitled) (Szociológiai Szemle, 2024)
The middle classes possess a material and economic position and symbolic capital which is better than the average in society, thus usually they may shape their life style with greater autonomy if compared to those of lower status. At the same time they jealously guard their relative well being and highly appreciate security. The paper studies whether the efforts of people living with a middle class sense of identity in family and marriage are characterised by their striving to achieve enhanced security? What is their opinion about living together outside marriage and about divorce destabilising family and life in marriage? The analysis confronts the opinion of middle class people with the practice followed by them.